Activity measurement of 222Rn gas for a key comparison. (April 2018) - Kim, B.J.; Lee, J.M.; Lee, K.B.; Park, T.S.; Kim, B.C.
Abstract: The Korea Research Institute of Standards and Science (KRISS) participated, in 2015, in an international Key Comparison (KC) of gaseous radon-222 activity named CCRI (II) -K2.Rn-222 to confirm international equivalence of KRISS-established gaseous radon-222 measurement standards. LNHB acted as KC pilot laboratory. This paper describes the KC measurement procedure followed at KRISS using the defined solid angle counting method together with auxiliary relative measurement methods and presents the results. Highlights: KRISS carried out KC measurement for gaseous 222 Rn activity. Defined solid angle counting method as the main measurement. Calibrated HPGe-detector was used for an ancillary measurement. Consistency of the main measurement was secured through the ancillary measurement.